Teaching for mathematical literacy in secondary and high schools in Lesotho: a didactic perspective - Mavugara-Shava, Fungai Munashe (University of the Free State, 2005)
The main purpose of this study is to inquire, from a didactical perspective, into the question of teaching mathematics for mathematical literacy in secondary and high schools in the district of Maseru, Lesotho. In the study, mathematical literacy and didactical practices relating to mathematics are viewed as related variables that directly impact upon each other. In order to appropriately place the concept of didactical practices in school mathematics education, the study engages support from literature to explore a range of related areas in mathematics education and in mathematical literacy. These areas include, amongst other factors, aspects such as: the position of mathematics in education, the role, meaning and neighbours of mathematics education, and the psychological theories and philosophies that influence trends in didactical practices related to mathematics. In the study, mathematical literacy itself is defined from different perspectives. In the light of these definitions, the study views mathematical literacy as the individual’s aggregate of mathematical skills and knowledge that empowers the individual to participate meaningfully and make well-founded mathematical judgements in a society that is imbued with technology. Didactical practices and the nature of mathematics that are purported to inculcate mathematical literacy in learners are discussed, in the study, to serve as a premise on which the teaching of mathematics, for mathematical literacy in secondary and high schools in the district of Maseru, is investigated. The investigation itself seeks to establish the current didactical practices relating to mathematics, which are employed in secondary and high schools in the district of Maseru, Lesotho, and to determine the extent to which these didactical practices correspond to and correlate with indicators of teaching mathematics for mathematical literacy. The study further examines whether the nature (content, objectives, and recommended didactical practices relating to mathematics) of the mathematics curriculum offered in the district of Maseru, concurs with that recommended in literature on teaching mathematics for mathematical literacy. In conclusion, the investigations of the study culminate in assessing which didactical practices relating to mathematics still need to be improved, embraced, or redefined. Recommendations based on the findings of the study include: the use of open-ended problem solving techniques, real-life problem investigations, and the use of projects as a didactical approach. Other recommendations are: themes across the school curriculum should be unified, real-life data should be used in statistics and probability, and mathematics problems should encompass actual, real-life problems rather than contrived problems related to real life situations.

Die hoofdoel met hierdie navorsing is om vanuit ’n didaktiese perspektief die vraag na die onderrig van wiskunde vir wiskundige geletterdheid in Lesotho se sekondêre en hoër skole na te vors. Wiskundige geletterdheid en wiskundig didaktiese praktyke word in hierdie navorsing as verwante veranderlikes beskou wat direk op mekaar inspeel. Ten einde didaktiese praktyke in wiskundeonderrig in skole toepaslik te plaas, verkry hierdie navorsing ondersteuning uit die literatuur om ’n reeks verwante gebiede in wiskundeonderrig en wiskundige geletterdheid te ondersoek. Hierdie areas sluit onder andere aspekte soos die volgende in: wiskunde se posisie in onderrig, die rol, betekenis en genote van wiskundeonderrig, die psigologiese teorieë en filosofieë wat tendense in wiskundige didaktiese praktyke beïnvloed. Wiskundige geletterdheid self word in hierdie navorsing vanuit verskillende perspektiewe gedefinieer. Die navorsing beskou wiskundige geletterdheid in die lig van hierdie definisies as die individu se totale wiskundige vaardighede en kennis wat hom/haar bemagtig om betekenisvol deel te neem en goedgefundeerde wiskundige oordele aan die dag te lê in ’n samelewing wat van tegnologie deurdrenk is. Die navorsing bespreek didaktiese praktyke en die aard van wiskunde wat na bewering wiskundige geletterdheid by leerders inskerp. Die bedoeling is dat dit dien as ’n vertrekpunt van waar die onderrig van wiskunde vir wiskundige geletterdheid in Lesotho se sekondêre en hoërskole ondersoek kan word. Die ondersoek self probeer vasstel wat die huidige wiskundig didaktiese praktyke is wat in sekondêre en hoërskole in Lesotho in gebruik is. Dit probeer ook vasstel in watter mate hierdie didaktiese praktyke met indikatore om wiskunde vir wiskundige geletterdheid te onderrig, ooreenstem en korreleer. Die navorsing ondersoek ve rder of die aard (inhoud, doelwitte en aanbevole wiskundig didaktiese praktyke) van die wiskunde-kurrikulum wat in Lesotho se sekondêre en hoërskole aangebied word ooreenstem met dit wat in die literatuur oor die onderrig van wiskunde vir wiskundige geletterdheid aanbeveel word, ooreenstem. Ten slotte loop die navorsingsondersoek uit op die assessering van watter wiskundig didaktiese praktyke nog verbeter, aanvaar of geherdefinieer moet word. Aanbevelings, wat op die bevindings van die navorsing gebaseer is, sluit in: die gebuik van oop probleemoplossingstegnieke, ondersoeke na probleemstellings in die werklike lewe en die gebruik van projekte as ’n didaktiese benadering. Ander aanbevelings is: temas in die skool-kurrikulum behoor verenig te word, data uit die werklike lewe behoort in statistiek en waarskynlikheid gebruik te word en wiskunde probleme behels werklike probleme uit die werklike lewe eerder as versinde probleme wat met situasies uit die werklike lewe verband hou.
Thesis (Ph.D. (Curriculum Studies))--University of the Free State, 2005
Keywords: Mathematics -- Study and teaching (Secondary) -- Lesotho